Efficacy of repetitive transcranial magnetic stimulation at different sites for peripheral facial paralysis: a prospective cohort study - Liu, Zicai; Wen, Xin; Shao, Yuchun; Wan, Zihao; Liu, Bangliang; Wang, Risheng; Liu, Huiyu (Frontiers in Neurology, 2023)
Background: There are very few studies on transcranial magnetic stimulation (TMS) therapy for facial paralysis and no studies comparing the efficacy of central and peripheral TMS in the treatment of peripheral facial paralysis (PFP).To observe the therapeutic effect and security of central and peripheral repetitive transcranial magnetic stimulation (rTMS) on PFP.Methods: Patients with unilateral onset of peripheral facial paralysis within one month were prospectively recruited, 97 patients with PFP were divided into the peripheral group, central group, and control group. The control group was given common treatment (drug therapy and acupuncture), and the peripheral and central groups received rTMS in addition to conventional treatment. After 2 weeks of treatment, the House-Brackmann (HB) grading scale, Sunnybrook facial grading system (SFGS), and modified Portmann scale (MPS) were used to evaluate the facial muscle function of patients in the three groups.Result: After 2 weeks of rTMS treatment, the HBGS/SFGS/MPS scores of the three groups were significantly better than before (P < 0.05), and the mean change values of HBGS, SFGS, and MPS scores were significantly higher in participants in Peripheral Group (P<0.001; P<0.001; P=0.003; respectively) and Central Group (P=0.004; P=0.003; P=0.009; respectively) than in Control Group.But the mean change values of HBGS, SFGS, and MPS scores showed no significant differences in participants in the Peripheral Group than in the Central Group (P=0.254; P=0.139; P=0.736; respectively) after 2 weeks of treatment (P > 0.05).Our study shows that rTMS can be a safe and effective adjuvant therapy for patients with PFP. Preliminary studies have shown that both peripheral and central stimulation can effectively improve facial nerve function, but there is no significant difference in the efficacy of the two sites.